Rituximab: How approval history is reflected by a corresponding patent filing strategy - Storz, Ulrich (Landes Bioscience, 2014)
Because drug development is not a static process, a drug’s market authorisation may change over time. In many cases, the number of indications for which a drug is approved increases. Because this facet of drug development also comes at significant costs, a corresponding patent filing strategy is required to protect these investments. The strategy as applied to rituximab, which is approved for a variety of indications, is discussed in this review.